Why Wikis in Foreign Language Teaching? - Medic, Branko; Sun, Xiaohui (The journal of contemporary issues in business and government, 2021)
The conventional teaching methods have been in practice for a number of decades and centuries but computers and technology has brought a revolution in the field of pedagogics in the past few years and the state of affairs in terms of teaching and learning can be now mapped on a big picture globally. The internet based resources such as podcasts, online forums, wikis and blogs have embellished the traditional face of education and enabled the learners as well as teachers to adapt to the online methods of learning and teaching. This new era of utilizing technology in the educational processes will broaden the vision of people regarding the acquisition of knowledge, its worldwide practical implications and furnish the every individual in the field of pedagogics with exceptional skills and motivation.